Health of the elderly : report of a WHO Expert Committee, meeting held in Geneva from 3 to 9 November 1987 - WHO Expert Committee on Health of the Elderly; World Health Organization (Geneva : World Health Organization, 1989)
An expert review of recent advances in knowledge about the biology of human aging, the special health needs of the elderly, and the present and future demands on health services. Representing the consensus reached by an international group of experts, the report concentrates on the many changes in skills, training, attitudes, policies, and services that will be needed to cope with the growing proportion of the elderly in the world population. Throughout, recommended changes are guided by the need to identify the specific interventions and policies most likely to increase the number of elderly who can achieve, in an undisabled state, their genetic potential for longevity. The report opens with an extensive analysis of research findings and conceptual models that shed light on the aging process and provide a background for identifying appropriate interventions and services. Specific topics discussed include the differences between intrinsic and extrinsic aging, the characteristic properties of illness in the elderly, the consequences of demographic aging in both industrialized and developing countries, and trends in the main causes of mortality and morbidity in selected groups of countries. Against this background, the report turns to a point-by-point review of progress in alleviating the main causes of morbidity and suffering among the elderly, including advances in understanding and managing falls, osteoporosis, visual and hearing impairments, changes in mental capacity, incontinence, stroke, and iatrogenic disorders. The next chapter, devoted to issues of health care, attempts to dispel some of the confusion surrounding the types of care, whether primary, family, or institutional, most appropriate to the needs of the elderly, social systems of support, and available resources. Other chapters provide estimates of future needs for personnel and training and consider the relationship between improving pension income and providing services. The report concludes with brief descriptions of health care policies for the elderly in Thailand and recent efforts to restructure services in the USSR.
1. Introduction -- 2. health and functional status -- 3. Progress in specific areas -- 4. Health care of elderly people -- 5. Personnel, education, and information dissemination -- 6. Balance between improving pension income and providing services -- 7. Conclusions and recommendations -- Acknowledgements -- References -- Selected reading -- Annexes
Keywords: Health Services for the Aged; Geriatrics; Health of the Elderly